Parallelism in the Diagnostic Performance of Bronchoscopic Sampling Techniques in Lung Carcinoma - D. Shah, Arti; Swati, Amrita; Malani, Swati; V. , Kusum Shah (International Journal of Psychosocial Rehabilitation, 2020)
Context: Flexible bronchoscopy is the recommended procedure for diagnosis of all suspected lung carcinoma, having sensitivity of 88% for central airway lesion and 78% for peripheral. The diagnostic yield of bronchoscopy combining various sampling techniques for visible lesions was predicted to be at least 80%. Aims: To compare the diagnostic yield of various sampling techniques of bronchoscopy in diagnosing lung carcinoma at a rural tertiary care center. Settings and Design: Retrospective observational study center in respiratory medicine at tertiary care. Methods and Material: 26 bronchoscopies done in radiologically suspected malignancy in the previous two and a half years were included. Histopathological or cytological evidence of malignant cells was considered as the final diagnosis of malignancy. Data of radiological and bronchoscopic findings and reports of sampling techniques were analyzed. Statistical analysis used: SPSS for Windows. Results: The overall diagnostic yield is 46.15%, while for central lesions it is higher than for peripheral lesions, 42.30 % and 7.69%, respectively. EBLB gave the highest diagnostic yield, 69.2%. BAL cytology is the most common procedure performed. Central lesions on imaging and visible endobronchial abnormalities like narrowing, intraluminal growth, and mucosal irregularity are predictors of higher diagnostic yield. Conclusions: The overall diagnostic yield in radiologically suspected lesions is 46.15%, and the highest diagnostic yield is with endobronchial lung biopsy. Central lesions on radiology and endobronchial abnormalities are strong predictors of high diagnostic yield, with the highest yield in biopsy amongst all techniques. Hence, a biopsy should be done in all such cases.